INDIGENOUS TERRITORIAL RECLAIMING IN BRAZIL: Centrality of the struggle of the A'uwē Xavante People - Maraiwatsede - Santos, Gilberto Vieira dos; Thomaz Junior, Antonio [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2024)
This article results from reflections developed in the doctoral thesis titled Indigenous Territorial Retakings: The A'uw & emacr; Xavante People of the Maraiwatsede Indigenous Land in Focus, which aims to contribute to unveiling the intricacies of the struggles of the Indigenous Movement in Brazil, especially in the pursuit of the realization of their territorial rights. The centrality of the Xavante people's struggle in the Maraiwatsede Indigenous Land expresses the process of Indigenous Retakings as the materialization of their struggles, and in this case, specifically, the victory achieved by this Indigenous People after four decades of resistance. In this article, we will focus on highlighting Indigenous resilience through the struggles rooted in the Indigenous Reclaiming Movements, as a phenomenon unique to these Peoples, with the aim of questioning the territorialities imposed by Capital and restoring expropriated territories.
Keywords: Maraiwatsede; Indigenous Retomada; Xavante; Territory; Original Right